La traduzione della parola altrui nel discorso giudiziario italiano e spagnolo, tra mediazione e ricodificazione (Altre Modernità, 2012)
This paper deals with the use of reported speech (RS) in Spanish criminal lawsuits (querellas) and police reports (denuncias) and argues about the most suitable strategies to translate such RS into Italian. In line of principle, the written record of the statements made by the individual(s) who filed the complaint is often the result of an oral cooperation between the plaintiff and the police officer and/or their attorney, whose subjectivity is reflected on the texts in a quite different fashion in the two legal cultures. The so-called ‘verbatim assumption’ of quotations in direct speech (DS) turns out to be a fallacy in the discussed genres, insofar as the locutor (i.e. the police officer or the attorney responsible for the drafting of the document) often normalizes the original utterances of the enunciator (i.e. the plaintiff whose point of view is represented in the report) in terms of cohesion, register and sentence length. Usually, these texts are translated following a strictly ‘interlinear approach’, so much so as to result almost illegible. An adequate command  of genre conventions – both in the source and in the target language – and the abidance by the translation universals of simplification and explicitation may help the translator produce a more efficient and readable target text, consistent with the expectations of a jurist in the target culture.